Long-Term Persistence of Anti-Poliovirus Antibody Titers After Two-Dose Booster Immunization with Conventional Inactivated Poliovirus Vaccine Among Japanese Adults: 10-Year Observational Study - Shinji Fukushima; Takashi Nakano; Minetaro Arita; Hiroyuki Shimizu; Atsuo Hamada (Vaccines)
Background/Objectives: Most Japanese adults received two doses of the oral polio vaccine (OPV) during childhood as part of the national immunization program. However, these two doses are considered suboptimal by global standards. The long-term persistence of anti-poliovirus antibodies after booster doses with the conventional inactivated poliovirus vaccine (cIPV) in Japanese adults remains unclear. This study was performed to evaluate long-term immunogenicity over a 10-year period following two cIPV booster vaccinations. Methods: Ten out of sixty-one adult participants in a short-term study were enrolled to assess the long-term immunogenicity of the booster vaccination. They underwent blood sampling at 3, 5, and 10 years after cIPV vaccination. Results: The results indicate that, even 10 years after the booster vaccination, antibodies against poliovirus types 1 and 2 remained at high levels, exceeding the detection limits of neutralization tests. However, some participants showed decreased antibody levels against poliovirus type 3. Conclusions: This study showed that cIPV boosters provided long-lasting protective immunity against poliovirus types 1 and 2 in adults who were vaccinated with OPV. These findings are valuable in assessing the need for IPV booster vaccinations in adults.